PROBLEMS AND SOLUTIONS IN DEVELOPING INCLUSIVE EDUCATION IN PRIMARY EDUCATION (Universal International Scientific Journal, 2026)
This article examines the goals and objectives of providing inclusive educationto children with disabilities. It also discusses the integration of children with special educationalneeds into society, as well as the problems in this field and possible solutions. In addition, theimportance of promoting inclusive education among teachers in primary education is highlighted.
Keywords: Inclusive education; upbringing; integration